A recombinant scFv antibody-based fusion protein that targets EGFR associated with IMPDH2 downregulation and its drug conjugate show therapeutic efficacy against esophageal cancer. (31st December 2022) - He, Shiming; Zhao, Chunyan; Tao, Hongyu; Sheng, Weijin; Gao, Ruijuan; Liu, Xiujun; Zhen, Yongsu
Abstract: The present study aimed to evaluate the anti-tumor efficacy of the epidermal growth factor receptor (EGFR)-targeting recombinant fusion protein Fv-LDP-D3 and its antibody-drug conjugate Fv-LDP-D3-AE against esophageal cancer. Fv-LDP-D3, consisting of the fragment variable (Fv) of an anti-EGFR antibody, the apoprotein of lidamycin (LDP), and the third domain of human serum albumin (D3), exhibited a high binding affinity for EGFR-overexpressing esophageal cancer cells, inhibited EGFR phosphorylation and down-regulated inosine monophosphate dehydrogenase type II (IMPDH2) expression. Fv-LDP-D3 was taken up by cancer cells through intensive macropinocytosis; it inhibited the proliferation and induced the apoptosis of esophageal cancer cells. In vivo imaging revealed that Fv-LDP-D3 displayed specific tumor-site accumulation and a long-lasting retention over a 26-day period. Furthermore, Fv-LDP-D3-AE, a pertinent antibody-drug conjugate prepared by integrating the enediyne chromophore of lidamycin into the Fv-LDP-D3 molecule, displayed highly potent cytotoxicity, inhibited migration and invasion, induced apoptosis and DNA damage, arrested cells at G2/M phase, and caused mitochondrial damage in esophageal cancer cells. More importantly, both of Fv-LDP-D3 and Fv-LDP-D3-AE markedly inhibited the growth of esophageal cancer xenografts in athymic mice at well tolerated doses. The present results indicate that Fv-LDP-D3, and Fv-LDP-D3-AE exert prominent antitumor efficacy associated with targeting EGFR, suggesting their potential as promising candidates for targeted therapy against esophageal cancer.